2007
DOI: 10.1152/japplphysiol.00630.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mucin secretion with MARCKS-related peptide improves airway obstruction in a mouse model of asthma

Abstract: Allergic asthma is associated with airway epithelial cell mucous metaplasia and mucin hypersecretion, but the consequences of mucin hypersecretion on airway function are unclear. Recently, a peptide derived from the myristoylated alanine-rich C kinase substrate protein NH(2)-terminal sequence (MANS) was shown to inhibit methacholine (MCh)-induced mucin secretion from airway mucous cells by >90%. We studied the effect of intranasal pretreatment with this peptide on specific airway conductance (sGaw) during chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 23 publications
(27 reference statements)
0
57
0
Order By: Relevance
“…Mucous metaplasia is a cardinal feature of the asthma phenotype that is thought to play a central role in death from asthma (24,25,31). Recent studies also suggest that mucin hypersecretion can contribute significantly to AHR (27,32,33). Thus, the finding that chronic administration of beta-blockers reduces mucin content in airway epithelial cells suggests a possible identification of a cell type involved in the decreased AHR that we previously observed (15).…”
Section: Discussionmentioning
confidence: 58%
“…Mucous metaplasia is a cardinal feature of the asthma phenotype that is thought to play a central role in death from asthma (24,25,31). Recent studies also suggest that mucin hypersecretion can contribute significantly to AHR (27,32,33). Thus, the finding that chronic administration of beta-blockers reduces mucin content in airway epithelial cells suggests a possible identification of a cell type involved in the decreased AHR that we previously observed (15).…”
Section: Discussionmentioning
confidence: 58%
“…This dissociation between IgE and AHR has been demonstrated in mast cell and B cell-deficient mice [52,53]. It is possible that the lack of mucus production seen in LPS-tolerant lungs contributes to the reduced airway resistance [54,55]. Further, airway sensitization has been shown to induce a strong Th17 response leading to robust AHR [56].…”
Section: Discussionmentioning
confidence: 98%
“…An obvious possibility is mucus plugging. Agrawal and coworkers (25) showed that treatment with a MARCKS-related peptide that blocks the release of mucin can ameliorate AHR in allergically inflamed mice. Presumably other components of the inflammatory exudates that accumulate in the airspaces of the asthmatic lung could also contribute to blockage of airways.…”
Section: Mechanisms Of Airway Closurementioning
confidence: 99%